Ibm PEMETAAN TOPOGRAFI LAHAN PONDOK PESANTREN TAHFIDZ RABBANIY KECAMATAN PERHENTIANRAJA KABUPATEN KAMPAR-RIAU - Fadrizal Lubis (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2022)
In today's era of infrastructure development, the need for the availability of topographic maps is unavoidable, especially if we are going to do the physical planning of buildings in an area or a location. Likewise, in carrying out the physical development of the Tahfizh Rabbaniy Islamic Boarding School, spatial information in the form of maps is needed. topography in the preparation or planning of the site plant in its construction. The method used is to make topographic measurements at the Tahfidz Rabbaniy Islamic Boarding School and has been carried out with the results obtained. . The location of the land is overgrown with weeds, grass and some palm oil. The highest elevation of +10.980 is at point D21 with coordinates X=31448.173, Y= 767651.050 and Z=10.980, and the lowest elevation of +8.803 is at point E139 coordinates X31381.662, Y=767679.797 and Z=8.803.